Mean Meridional air-motion and associated transport process in the atmosphere - RAO, M. S. V. (MAUSAM, 1963)
Eliassen's equation of quasi-static balance has been rederived in a more suitable frame of co-oridinates and, by making certain simplyfying assumptions, rendered into a form which lends itself easily to solution by relaxation. The differential equation thus obtained is solved for extended sources of heat and momentum similar to those actually encountered in the troposphere. The results show a mean meridional circulation consisting of a strong direct cell in low latitudes and a week indirect cell in the middle latitudes. In section 3 of the paper, starting from the idea that the mean meridional circulation is split up into cells and making use of the values of the strength of the circulation deduced by Tucker and Mintz, the sources and sinks of heat and momentum necessary to maintain such mean motion are evaluated. Further, an attempt is made to infer what the character of eddy motion in the meridional plane has to be in order to satisfy balance requirements.